"Doing It" in the Kitchen: Rhetorical Field Methods, Arts/Practice-Based Research, and Queer Archives. (February 2021) - Beck, Sarah Lindsey
Everyday domestic spaces, such as kitchens, are often crucial to the understanding of practices and discourses of queer and other marginalized communities. However, due to the private nature of these spaces, they can be difficult for rhetorical critics and others to access. This article offers arts/practice-based research as an intervention into rhetorical field methods (RFM) as a means of accessing and engaging with private, often inaccessible places, such as kitchens. In addition, arts/practice-based methods can expand the notion of "doing" rhetoric and co-creation with participants, which result in the creation of subject formations and alternative, collaborative, and affective archives. Such building of collective queer archives is essential, I argue, in that it helps to not only document the "stuff" of queer lives but also capture fleeting and affective moments of queer collisions and becomings. In addition, arts/practice-based research methods can aid researchers to generate knowledge and archives related to underrepresented aspects of queer lives. To engage with queer domestic spaces and the intersection of RFM and arts/practice-based research, I reflect on Autostraddle.com 's "Queer in the Kitchen" gallery, my participation in the creation of this text, and the development of my own gallery Queering the Kitchen.